Digital age as ethical maze: citizen journalism ethics during crises in Zimbabwe and South Africa - Moyo, Last (Routledge, 2021)
This article discusses citizen journalism ethics in crisis settings. It argues for an ontological critique of citizen journalism ethics where the practice must not be judged in relation to the moral taboos of mainstream journalism. Situating citizen journalism within the broader context of liquid modernity and networked practices, the article argues that the practice marks the rise of personalised ethics and morality without ethical codes. Citizen journalism ethics in crisis settings are seen as ambivalent, nascent, fluid, individualised, situational, and sometimes contradictory. The personalisation of ethics also means that professional codes of conduct shift from codes to individual moral impulses in a complex melange of the deontic, virtuous and teleological, that is informed by higher-order ethics of freedom, human rights, social justice, media pluralism and citizen participation. Using case study and discourse analysis methods, the article concludes that citizen journalism represents something that remains deeply futuristic, where ethics are likely to crystallise around deprofessionalised and deinstitutionalised personal responsibilities.